2007
DOI: 10.1007/s10750-007-0752-0
|View full text |Cite
|
Sign up to set email alerts
|

Invasion biology of Ponto-Caspian onychopod cladocerans (Crustacea: Cladocera: Onychopoda)

Abstract: We review the patterns of recent range expansions and the biology of the invasive PontoCaspian predatory onychopod cladocerans: Cercopagis pengoi, Evadne anonyx, Podonevadne trigona, Cornigerius maeoticus and Cornigerius bicornis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…For example, invasive predatory onychopods have significantly reduced zooplankton species richness in the Great Lakes of North America (Yan et al, 2002) o n l y -group (Belyaeva and Taylor, 2009). o n l y (Gorokhova et al, 2000), and in a large artificial reservoir on the Volga River, Russia (Panov et al, 2007). The most famous cladoceran invaders are species of Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, invasive predatory onychopods have significantly reduced zooplankton species richness in the Great Lakes of North America (Yan et al, 2002) o n l y -group (Belyaeva and Taylor, 2009). o n l y (Gorokhova et al, 2000), and in a large artificial reservoir on the Volga River, Russia (Panov et al, 2007). The most famous cladoceran invaders are species of Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because the models (especially those derived from CT) identify thresholds, they may serve as useful predictors for shifting environmental factors. It has been recently demonstrated that, like many other organisms, zooplankton are affected by climate change (e.g., southern species and assemblages moving into northern regions- Beaugrand et al 2002;Panov et al 2007;Sullivan et al 2007). A warming climate is also projected to increase salinity in estuaries and coastal areas, with accompanying changes in the likelihood of non-native species becoming established (Rahel and Olden 2008).…”
Section: Discussionmentioning
confidence: 99%
“…5; Table S1). In contrast to C. pengoi, E. anonyx has no prior invasion history in freshwater (Panov et al 2007) and is encountered in quite a narrow range of salinities in its native origin (Table S1). Both species prefer warm waters but are adapted to wide fluctuations in temperature in their native areas (Rivier 1998).…”
Section: Onychopod Cladoceransmentioning
confidence: 99%
“…have become more abundant in the Gulf of Finland and Gulf of Riga during recent decades and this has been partially accounted for mild winters and warmer summers. Panov et al (2007) have suggested that non-indigenous zooplankton species have positively responded to changes in climatic conditions of the recent past, allowing these species to reproduce and establish in the Baltic Sea. However, no studies on the impacts of both temperature and salinity changes on multiple non-indigenous species, have been published for the Baltic Sea, although many native species have been assessed for future changes (Vuorinen et al 2015).…”
Section: Introductionmentioning
confidence: 99%